PENGARUH TUNJANGAN TRANSPORTASI TERHADAP MOTIVASI KARYAWAN PADA PT. MULTI INDOMANDIRI (WINGS GROUP) - Urika, Urika; Nurfarisyi, Muhamad Ikhsan (Universitas Banten Jaya, 2023)
An organization or company will try to take various actions to achieve company goals. Employees are the main factor in achieving these goals. The more employees who are motivated to do something, the better it is for the organization or company to make it easier to achieve its goals. Sometimes, other variables can cause the resource's motivation to decrease. therefore, to find out how transportation allowances affect PT. Multi Indomandiri (Wings Group) is the aim of this research. The quantitative approach method used in making this research by taking a sample of seventy workers in the production division of PT. Multi Indomandiri (also known as Wings Group). This study uses simple linear regression analysis using classical assumption test, model significance, and model quality test. That the transportation allowance has a positive and significant influence on the motivation of PT. Multi Indomandiri (Wings Group) as a result of this research